Pragmatics representation in the drawings of students of the Art Education Department (Al-Academy, 2019)
The current research aims to reveal the representations of pragmatics in models of art education students' drawings, by first investigating pragmatics references as a critical approach that can be addressed to examine the achieved tangible achievement and the nature of the brand's work in its social space in light of the brand between it and the users of this relationship that is determined by the cultural reference of the brand's consumer, in addition to the differences between the presence of the brand between its semiotic framework and its pretexts imposed by pragmatics. Perhaps the critical approaches here led to transforming the brand from its linguistic context to the visual context that calls for new mechanisms to employ the brand in the visual achievement, or by looking at its use critically in the social, psychological and cultural space, as imposed by the context and the new critical data and the major transformations indicated by the objective exterior, which led to the transformation from text to discourse. After the theoretical introductions, a number of artistic works were selected and placed under critical dissection in order to achieve the desired goal, which was shown by some of the results that the research concluded, and to harmonize between the theoretical statements of the text and the procedural applications in the practical models as a sample that can be relied upon to achieve the goal.